Immobilization of laccases from Pycnoporus sanguineous on magnetized carbon nanofibers for the degradation of psychiatric drugs: venlafaxine and carbamazepine - Hernández Martínez, Saúl Antonio; Balderas-Saucedo, Alberto; González-González, Reyna Berenice; Parra-Saldívar, Roberto; Vazquez-Duhalt, Rafael; Melchor-Martínez, Elda M. (Elsevier, 2025)
The COVID-19 pandemic has significantly increased the consumption of psychiatric medications, such as venlafaxine (VFX) and carbamazepine (CBZ), leading to their accumulation in wastewater and subsequent environmental concerns. These compounds are classified as emerging pollutants, presenting challenges for conventional wastewater treatment systems. This study, faced the immobilization of laccases derived from a native strain of Pycnoporus sanguineus CS43, isolated from northeastern Mexico, onto magnetically modified carbon nanofibers (mCNF) to enhance degradation efficiency, enzyme stability, and reusability. The enzyme immobilization on mCNF resulted on high loading value of 73.24%. The performing of the degradation assays revealed that this innovative system achieved 51.51% and 57.14% removal of VFX and CBZ respectively within just 4 h at pH 5 and 25°C. A remarkable stability of the system was demonstrated retaining between 70% and 100% the enzyme activity on the nanomaterial. After 28 days of storage, the nanobiocatalysts system retained 74.50% of their initial activity. These results highlight the potential of mCNF as an effective support for laccase immobilization, providing a sustainable and efficient strategy for the bioremediation of psychiatric drug pollutants in aquatic environments.
Keywords: 40 Engineering; Biocatalysis; Enzyme immobilization; Laccases; Nanobiocatalysts; Nanofibers